2012
DOI: 10.1177/0974909820120108
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Maxillomandibular Sagittal Relationship and Pharyngeal Airway Passage Dimensions

Abstract: Objectives: To test the hypothesis that there is no association between sagittal maxillomandibular relationship and pharyngeal airway passage dimensions. Materials and methods: Lateral cephalograms of 90 subjects were used to measure the upper pharyngeal airway. The subjects were divided into three groups (each group included 30 subjects) according to ANB angle: Class III (ANB < 0.7°); Class I (ANB > 0.7° and < 4.7°); Class II (ANB > 4.7°). All lateral cephalograms were traced manually. Results: The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
(30 reference statements)
2
4
0
3
Order By: Relevance
“…23 The literature also showed that individuals with skeletal Class III and I had greater dimensions of the oropharynx and the laryngopharynx as well as palatopharynx, as compared with individuals with skeletal Class II. 24,25 Such relations were confirmed by another study. 22 Only the values of the laryngopharyngeal dimensions did not differ significantly among the given skeletal classes.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…23 The literature also showed that individuals with skeletal Class III and I had greater dimensions of the oropharynx and the laryngopharynx as well as palatopharynx, as compared with individuals with skeletal Class II. 24,25 Such relations were confirmed by another study. 22 Only the values of the laryngopharyngeal dimensions did not differ significantly among the given skeletal classes.…”
Section: Introductionsupporting
confidence: 59%
“…23 W piśmiennictwie wykazano także, że osoby odpowiednio z III i I klasą szkieletową mają większe wartości wymiarów części ustnej i krtaniowej gardła oraz palatopharynx w odniesieniu do osób z II klasą szkieletową. 24,25 W innym badaniu potwierdzono powyższe zależności. 22 Jedynie wartości wymiarów krtaniowej części gardła nie różniły się istotnie pomiędzy określonymi klasami szkieletowymi.…”
Section: Introductionunclassified
“…The literature supports the claim that subjects with a retrognathic mandible have decreased airway dimensions. 30,31 A lowered posture of the tongue depicted in our study after TBA therapy minimizes the chance of collapsibility of the velopharynx; this occurs as a result of the tongue being attached to the lateral walls of the soft palate via the palatoglossal arch. 32 The gravitational influence of the tongue on the soft palate, though weak in nature, is also reduced by its lowered posture and, in effect, increases the airflow.…”
Section: Resultsmentioning
confidence: 85%
“…Faring berbentuk tabung dan memanjang secara superoinferior dari dasar tengkorak menuju dataran inferior dari vertebra servikalis ke enam. 5,6 Faring dapat dibagi menjadi tiga bagian: nasofaring (epifaring), orofaring (mesofaring) dan laringofaring (hipofaring) yang menghubungkan rongga hidung, rongga mulut dan laring pada faring. 7,8 Abnormalitas pada struktur kraniofasial, seperti defisiensi mandibula, retrusi bimaksila, dataran oklusal yang curam, peningkatan sudut dataran mandibula dan posisi tulang hyoid yang lebih ke posterior menyebabkan penyempitan saluran udara faring.…”
Section: Pendahuluanunclassified
“…7,8 Abnormalitas pada struktur kraniofasial, seperti defisiensi mandibula, retrusi bimaksila, dataran oklusal yang curam, peningkatan sudut dataran mandibula dan posisi tulang hyoid yang lebih ke posterior menyebabkan penyempitan saluran udara faring. 5,9,10 Penelitian perbedaan yang tidak signifikan pada nasofaring dan laringofaring antara kelompok Kelas I, II dan III skeletal, namun pada orofaring ditemukan perbedaan yang signifikan. Eslamian dkk., dan Lopatiene dkk., menemukan perbedaan yang signifikan pada lebar nasofaring, orofaring dan laringofaring antara Kelas skeletal yang berbeda, hal ini mungkin disebabkan oleh penelitian Eslamian dkk., yang meneliti sampel dengan pola pertumbuhan vertikal yang normal sedangkan penelitian Lopatiene dkk., menggunakan metode pengukuran yang berbeda dengan rentang usia sampel 7-17 tahun.…”
Section: Pendahuluanunclassified